Novel volumetric analysis for stent expansion after drug‐eluting stent implantation: An optical coherence tomography study. Issue 5 (23rd March 2020) - Katsura, Aritomo; Minami, Yoshiyasu; Kato, Ayami; Muramatsu, Yusuke; Sato, Toshimitsu; Hashimoto, Takuya; Meguro, Kentaro; Shimohama, Takao; Ako, Junya
Abstract: Objectives: To assess the clinical significance of a novel optical coherence tomography (OCT)‐derived volumetric parameter of stent expansion by comparing it with the conventional parameters in real‐world practice. Background: The clinical significance of novel parameters in real‐world practice including longer and smaller stents remains to be elucidated. Methods: A total of 226 de novo lesion treated with drug‐eluting stents in 208 consecutive patients were enrolled. Stent expansion was retrospectively assessed on the final OCT images after stent implantation. The novel parameter was the minimum expansion index (MEI) calculated using a novel algorithm that yields the ideal lumen area in each frame by taking into account vessel tapering. The device‐oriented clinical end point (DoCE) included cardiac death, target vessel‐related myocardial infarction, ischemia‐driven target lesion revascularization. Results: The MEI in the lesions with a DoCE ( n = 22) at 2 years and cases without a DoCE ( n = 204) was 64.3 ± 12.0% and 78.5 ± 14.6%, respectively ( p < .001). In the receiver operating characteristic curve analyses, the areas under the curve for the MEI (0.787; p < .001) were larger than that for %stent expansion (0.718; p = .001) and minimum stent area (0.664; p = .004) in predicting the DoCE. The best cutoff of MEI for predicting the DoCE was 74.0. Conclusions: The novel MEI was better than the conventional %stent expansion and minimum stent area for predicting DoCE.